Kajian Perbandingan Bantalan Elastomer Sebagai Perletakan Jembatan dengan Menggunakan 4 Lapisan dan 3 Lapisan Pelat Baja - N. Retno Setiati; Rully Ranastra Irawan (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
In generally bridge bearing in Indonesia is made from metal, in the case of quality of materials and also installation method often generate problems. This metal bearing pad relatively more expensive and its wight enough heavily in the case of transportation. In Indonesia, the elastomeric bridge bearing have been used. The experiments which have been done to the Experi mental Stationer of Bridge and Road Furniture, Research Technology of Rubber in Bogor, and Produser of Rubber have earned to make laminated elastomeric bridge bearings which made from natural rubber and synthetic rubber according to spesification which have been determined by Standard – Spesification like AASHTO. This spesification required to be taken care of elastomeric bridge bearings which produced do not become problems in periode to come.